2005
DOI: 10.1038/sj.bjc.6602904
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cytoplasmic and nuclear Survivin in primary and secondary human glioblastoma

Abstract: Clinically, human glioblastoma (GBM) may develop de novo or from a low-grade glioma (secondary GBM), and molecular alterations in the two pathways may differ. This study examined the status of Survivin expression and apoptosis in 30 primary and 26 secondary GBMs. Our results show that cytoplasmic Survivin positivity was significantly (Po0.001) more frequent in primary GBMs (83%) than that in secondary GBMs (46%). In addition, an inverse correlation of cytoplasmc Survivin positivity with GBM apoptotic index, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 28 publications
3
56
0
1
Order By: Relevance
“…in regards to potential prognostic factors, nuclear or cytoplasmic survivin has been demonstrated to be an unfavorable prognostic marker in several types of tumors, while other studies have described nuclear or cytoplasmic survivin as a favorable prognostic marker (20)(21)(22)(23)(24). in our study, the statistical analysis showed that the patients whose tumors did not express survivin had a better outcome compared to survivin-positive tumors in terms of either DFS or OS.…”
Section: Discussionsupporting
confidence: 46%
“…in regards to potential prognostic factors, nuclear or cytoplasmic survivin has been demonstrated to be an unfavorable prognostic marker in several types of tumors, while other studies have described nuclear or cytoplasmic survivin as a favorable prognostic marker (20)(21)(22)(23)(24). in our study, the statistical analysis showed that the patients whose tumors did not express survivin had a better outcome compared to survivin-positive tumors in terms of either DFS or OS.…”
Section: Discussionsupporting
confidence: 46%
“…Recently, a critical role for survivin in the control of autophagy was also reported [8] . Survivin, normally expressed during embryonic and fetal development, is downregulated in adult tissues and overexpressed in a variety of human cancers [9][10][11][12] . Inhibition of apoptosis by survivin is a predictor of poor prognosis and shorter survival in patients suffering from various carcinomas [13] .…”
Section: Topic Highlightmentioning
confidence: 99%
“…However, despite the plethora of data collected, the prognostic significance of the subcellular distribution of survivin in cancer remains unclear. In 2005 a review of the subject returned a hung jury, revealing more opposing conclusions and contradictions than commonalities (Li et al, 2005); see also (Xie et al, 2006). As most of these clinical-based studies used histopathological samples, the lack of uniformity in sample collection and preservation between labs, together with differences in antibody protocols and the subjective nature of the analysis are likely to have contributed to the variation within these data (Li et al, 2005).…”
Section: Subcellular Localisation Of Survivin As a Prognostic Marker mentioning
confidence: 99%